2017
DOI: 10.18488/journal.aefr.2017.710.972.980
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Intentions: A Study on Students from Countryside University

Abstract: Article HistoryThis study aims at evaluating the outlook of the students, who are studying at a countryside institution in a developing country, towards entrepreneurship by applying the theory of planned behavior. Taking into account the lack of employment opportunities in rural areas in developing economies, and the scarcity of literature on students' self-employment intentions there; we find this study timely. The results show that there is positive outlook of the respondents toward self-employment, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
4
7
0
Order By: Relevance
“…The findings are consistent with earlier studies which have supported the influence of subjective norms on EI among students (Codrina et al , 2012; Davis, 2017; Haque et al , 2017; Iakovleva et al , 2011; Ilesanmigbenga, 2017; Kautonen et al , 2015; Lo et al , 2012; Shirokova et al , 2018; Solesvik, 2017). However, the findings contradict previous research (Ali et al , 2014; Bayon et al , 2015; Esfandiar et al , 2017; Juan et al , 2005; Robledo et al , 2015; Santos et al , 2016; Zhang et al , 2014) which showed that PSN was a weak predictor of EI.…”
Section: Discussionsupporting
confidence: 92%
“…The findings are consistent with earlier studies which have supported the influence of subjective norms on EI among students (Codrina et al , 2012; Davis, 2017; Haque et al , 2017; Iakovleva et al , 2011; Ilesanmigbenga, 2017; Kautonen et al , 2015; Lo et al , 2012; Shirokova et al , 2018; Solesvik, 2017). However, the findings contradict previous research (Ali et al , 2014; Bayon et al , 2015; Esfandiar et al , 2017; Juan et al , 2005; Robledo et al , 2015; Santos et al , 2016; Zhang et al , 2014) which showed that PSN was a weak predictor of EI.…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study run contrary to the findings of Kruegar et al (2000, in USA) [1], and Kuttim et al, 2014 [28], whose study of 17 European countries showed that subjective norm does not have significant effect on entrepreneurial intentions. The result is, however, consistent with findings of Tegtmeier (2012) [15], Liñán & Chen, 2009 [29], and the recent studies such as Haque et al, 2017 [30]. The unique disclosure of the present study is that subjective norm accounts for more variance in entrepreneurial intention than perceived behavioral control.…”
Section: Discussionsupporting
confidence: 93%
“…Students are more likely to be interested in entrepreneurship when they think it will lead to the desired results, it will gain the approval of others (Mmakgabo 2014). The decision to start an entrepreneurial activity is to a greater extent determined by the motivation of opportunity, rather than the motivation of necessity (Herrington & Kew 2017;Maque 2017). The data in Table 5 show that students from Latvia in the pandemic would rather plan their business in such areas as advertising/marketing/design (19.7%), trade (wholesale/retail) (12.3%), education (11.5%).…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%